2010
DOI: 10.1186/1471-230x-10-20
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal imbalances are uncommon in chagasic megaesophagus

Abstract: BackgroundChagas' disease is a human tropical parasitic illness and a subset of the chronic patients develop megaesophagus or megacolon. The esophagus dilation is known as chagasic megaesophagus (CM) and one of the severe late consequences of CM is the increased risk for esophageal carcinoma (ESCC). Based on the association between CM and ESCC, we investigated whether genes frequently showing unbalanced copy numbers in ESCC were altered in CM by fluorescence in situ (FISH) technology.MethodsA total of 50 forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Interestingly, a previous study analyzed a series of CM, also from the same region of the present study, for the presence of genomic imbalances in genes relevant in esophageal carcinogenesis, and any significant event was observed. 22 So, TP53 mutations in the conjugation other etiological factors may contribute to cancer development. In fact, our observation of a higher consumption of alcohol and tobacco observed in the ESCC/CM group in comparison with the CM group, supported this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a previous study analyzed a series of CM, also from the same region of the present study, for the presence of genomic imbalances in genes relevant in esophageal carcinogenesis, and any significant event was observed. 22 So, TP53 mutations in the conjugation other etiological factors may contribute to cancer development. In fact, our observation of a higher consumption of alcohol and tobacco observed in the ESCC/CM group in comparison with the CM group, supported this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…8,[19][20][21] The studies evaluating the molecular mechanisms underlying this carcinogenic process are scarce. 22 TP53 tumor suppressor gene exhibited a major role in the tumorigenesis of ESCC. 23 TP53 is, by far, the highest mutated gene, with frequencies varying between studies and population, and recently, whole genome sequencing analysis, confirm the high frequency (≈60%) of TP53 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…A study examined cytogenetic alterations in patients with chagasic megaesophagus and observed aneuploidies of chromosomes 7, 11, and 17 in 60% and the deletion of the oncogene p53 in 54.5% of 20 study patients; this might increase the risk of tumor development (Manoel-Caetano et al, 2004). While point mutations in exonic regions of p53 , FHIT (fragile histidine triad gene) and CDKN2A (cyclin-dependent kinase Inhibitor 2A) genes or genomic imbalances were not frequent in chagasic megaesophagus, a silent mutation in exon7 of the FHIT gene and copy numbers of the CDKN2A and CEP9 (C-terminally encoded peptide 9) genes might be involved in esophageal carcinogenesis (SM-C et al, 2009, Bellini et al, 2010). The assumed T. cruzi -related carcinogenesis is most likely due to host genetic factors, and the parasite-host interaction resulting in chronic inflammation in particular tissues (Fig.…”
Section: Paradoxical Dual Impacts Of Chagas Disease In Carcinogenesismentioning
confidence: 99%
“…Chagas' disease comprises three phases: an acute phase, usually asymptomatic, a long silent period and finally some patients develop a chronic disease, in which the disease becomes evident with the appearance of cardiac dysfunction, and enlargement of some organs (colon and esophagus, 6-7%) (Bellini et al, 2010). Despite the intense efforts made to develop efficient antiparasitic drugs, an effective treatment for Chagas' disease is still lacking.…”
Section: Introductionmentioning
confidence: 99%